2001
DOI: 10.1136/fn.85.2.f105
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of newborn screening for medium chain acyl-CoA dehydrogenase deficiency in 275 000 babies

Abstract: Objective-To evaluate newborn screening by tandem mass spectrometry for detection of medium chain acyl-CoA dehydrogenase (MCAD) deficiency, a fatty acid oxidation disorder with significant mortality in undiagnosed patients. Design-The following were studied: (a) 13 clinically detected MCAD deficient subjects, most homozygous for the common A985G mutation, whose newborn screening sample was available; (b) 275 653 consecutive neonates undergoing routine newborn screening. Screened infants with blood octanoylcarn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
84
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(86 citation statements)
references
References 23 publications
0
84
2
Order By: Relevance
“…Typically, homozygotes produce a C8 concentration in the range of 4 -10 mol/L, although some compound heterozygotes will also produce these concentrations. Generally, compound heterozygotes produce lower C8 concentrations, in the range 1-4 mol/L in newborn specimens (15 ). Although C8 is the metabolite of primary interest in detecting MCAD deficiency by MS/MS, it is important to note that severity of disease is not easily predicted based solely on C8 concentration (95,103 ).…”
Section: C2mentioning
confidence: 99%
“…Typically, homozygotes produce a C8 concentration in the range of 4 -10 mol/L, although some compound heterozygotes will also produce these concentrations. Generally, compound heterozygotes produce lower C8 concentrations, in the range 1-4 mol/L in newborn specimens (15 ). Although C8 is the metabolite of primary interest in detecting MCAD deficiency by MS/MS, it is important to note that severity of disease is not easily predicted based solely on C8 concentration (95,103 ).…”
Section: C2mentioning
confidence: 99%
“…145 Recent molecular studies performed as follow-up to newborn screening by MS/MS technology have found a lower percentage of individuals with the common A985G mutation. 136,146 A second common mutation (T199C) has been observed in US populations identified initially by MS/MS screening. The T199C mutation is a mild mutation that produces a biochemical phenotype but has never been observed in clinically affected patients.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…135 Incidence MCAD deficiency has been diagnosed almost exclusively among individuals of northwestern European origin, with frequencies ranging from 1 in 46 000 to 1 in 6400. 136,137 The heterozygote frequency is 1% to 2%. A few cases have been identified in other populations, including one Pakistani patient, one black patient, and isolated cases in individuals of Southern European and Northern African origin.…”
Section: Medium-chain Acyl-coa Dehydrogenasementioning
confidence: 99%
“…Previous studies have reported that acylcarnitine profiles in premature and VLBW infants differ from profiles of babies born at term or of normal birth weight (7,12 ). Were this the case, it might pose a problem in interpreting results from screening programs (4,13 ). We have demonstrated, however, that, at the population level, C8 concentrations do not vary by prematurity or birth weight over the first 2 weeks of life.…”
Section: Discussionmentioning
confidence: 99%